A Coupled Gas Flow-Mechanical Damage Model and Its Numerical Simulations on High Energy Gas Fracturing - Yu Bai; Li Sun; Chenhui Wei (Geofluids)
High-energy gas fracturing (HEGF) and gas fracturing (GF) are considered to be efficient to enhance the permeability of unconventional gas reservoir. The existing models for HEGF mainly focus on the dynamic loading of stress wave or static loading of gas pressurization, rather than on the combined actions of them. Studies on the combination of HEGF and GF (HEGF+GF) are also few. In this paper, a damage-based stress wave propagation-static mechanical equilibrium-gas flow coupling model is established. Numerical model and determination of mesomechanical parameters in finite element analysis are described in detail. Numerical simulations on crack evolution under HEGF, GF, and HEGF+GF are carried out, and the impact of in situ stress conditions on crack evolution is discussed further. A total of 11 cracks with length of 2.3-4 m in HEGF, 4 main cracks with length of 6.5–8 m in GF, and 11 radial cracks with length of 2–11.5 m in HEGF+GF are produced. Many radial cracks around the borehole are formed in HEGF and extended further in GF. The crustal stress difference is disadvantageous for crack complexity. This study can provide a reference for the application of HEGF+GF in unconventional gas reservoirs.